A real-world study on the treatment of extremely preterm infants: a multi-center study in southwest area of Fujian Province in China - Liang Gao; Dong-mei Chen; Hui-ping Yan; Li-ping Xu; Shu-zhen Dai; Rong-hua Zhong; Qi-bing Chen; Si-min Ma; Xin-zhu Lin (BMC, 2024)
Abstract Background Due to regional and cultural differences, the current status of extremely preterm infants(EPIs) treatment across different areas of mainland China remains unclear. This study investigated the survival rate and incidence of major diseases among EPIs in the southwest area of Fujian province. Method This retrospective and multicenter study collected perinatal data from EPIs with gestational ages between 22-27+ 6w and born in the southwest area of Fujian province. The study population was divided into 6 groups based on gestational age at delivery. The primary outcome was the survival status at ordered hospital discharge or correct gestational age of 40 weeks, and the secondary outcome was the incidence of major diseases. The study analyzed the actual survival status of EPIs in the area. Result A total of 2004 preterm infants with gestational ages of 22-27+ 6 weeks were enrolled in this study. Among them, 1535 cases (76.6%) were born in the delivery room but did not survive, 469 cases (23.4%) were transferred to the neonatal department for treatment, 101 cases (5.0%) received partial treatment, and 368 cases (18.4%) received complete treatment. The overall all-cause mortality rate was 84.4% (1691/2004). The survival rate and survival rate without major serious disease for EPIs who received complete treatment were 85.1% (313/368) and 31.5% (116/318), respectively. The survival rates for gestational ages 22-22+ 6w, 23-23+ 6w, 24-24+ 6w, 25-25+ 6w, 26-26+ 6w, and 27-27+ 6w were 0%, 0%, 59.1% (13/22), 83% (39/47), 88.8% (87/98), and 89.7% (174/198), respectively. The survival rates without major serious disease were 0%, 0%, 9.1% (2/22), 19.1% (9/47), 27.6% (27/98), and 40.2% (78/194), respectively. Conclusion The all-cause mortality of EPIs in the southwest area of Fujian Province remains high, with a significant number of infants were given up after birth in the delivery room being the main influencing factor. The survival rate of EPIs who received complete treatment at 25-27 weeks in the NICU was similar to that in developed countries. However, the survival rate without major serious disease was significantly lower compared to high-income countries.